2022
DOI: 10.1186/s12943-022-01650-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived exosomes in cancer therapy resistance: recent advances and therapeutic potential

Abstract: Mesenchymal stem cells (MSCs) are multipotent stromal cells that can be obtained from various human tissues and organs. They can differentiate into a wide range of cell types, including osteoblasts, adipocytes and chondrocytes, thus exhibiting great potential in regenerative medicine. Numerous studies have indicated that MSCs play critical roles in cancer biology. The crosstalk between tumour cells and MSCs has been found to regulate many tumour behaviours, such as proliferation, metastasis and epithelial-mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 156 publications
0
41
0
Order By: Relevance
“…EV can be obtained from a variety of specimens, including cell culture supernatants and various body fluids, such as blood and urine ( Logozzi et al, 2020 ). MSC-derived EV play an increasingly important role in intracellular communication and tissue repair ( Joo et al, 2020 ; Lin et al, 2022 ). Compared with living cells, their clinical application may offer significant advantages because they may reduce adverse side effects after application, as well as infusion toxicity, uncontrolled cell growth, and possible tumor formation ( Liang et al, 2014 ; Qiu et al, 2019 ; Weng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EV can be obtained from a variety of specimens, including cell culture supernatants and various body fluids, such as blood and urine ( Logozzi et al, 2020 ). MSC-derived EV play an increasingly important role in intracellular communication and tissue repair ( Joo et al, 2020 ; Lin et al, 2022 ). Compared with living cells, their clinical application may offer significant advantages because they may reduce adverse side effects after application, as well as infusion toxicity, uncontrolled cell growth, and possible tumor formation ( Liang et al, 2014 ; Qiu et al, 2019 ; Weng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EMT weakens the strong adhesion between differentiated epithelial cells, allowing cancer cells to achieve individual or collective motility, which makes EMT an intuitive mechanism for tumor metastasis initiation (107)(108)(109). Exosomes can be involved in the EMT effect of tumor cells (110)(111)(112).…”
Section: Role Of Exosomes In Nsclc Metastasismentioning
confidence: 99%
“…Multiple lines of research have so far indicated that MSC-Exos are involved in a multitude of mechanisms that could lead to either the promotion or attenuation of cancer treatment resistance. It has been found that the MSC-Exos could enhance therapeutic sensitivity in several cancers, including lymphoma, breast cancer ovarian cancer, gastric cancer, and hepatocellular carcinoma [ 121 ]. Mechanistically, MSC-Exos hinder the development of these cancers through the inhibition of tumor proliferation and angiogenic pathways, and through the stimulation of apoptosis.…”
Section: Molecular Mechanisms Of Exosomesmentioning
confidence: 99%